(3GdWQb GdeSJMOKI dJHGOd ChQGb GdeQGaYGJ (B: s (3OQGSI ebGQfI (B/ s - (3QVhi eLOi TGcQ YHOGdMejOs; (3CSGeI CMeO Thbi GdedjLi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JfGhd ehVhY GdQSGdI GdWQb GdeSJMOKI dJHGOd ChQGb GdeQGaYGJ(B. (3h bO YGdLJ GdQSGdI Pdc GdehVhY ai bSejf(B: (3JfGhd GdbSe GdChd eaJQVGJ YedjI GdJHGOd hPdc aj HGHjf, MjK JfGhd GdHGH GdChd HMK GdQcf GdTNUi dYedjI GdJHGOd h GdeJeKd ai CTNGU h CWQGa GdNUheI GdbVGFjI ai GdbGfhf GdeUQi h GdaQfSi JHGYG(B. (3h JfGhd GdHGH GdKGfi GdQcf GdeGOi dYedjI GdJHGOd h GdeJeKd ai ChQGb GdeQGaYGJ(B. (3Ke HYO Pdc, JfGhd GdbSe GdKGfi OQGSI GdjGJ YedjI JHGOd GhQGb GdeQGaYGJ h Pdc ai HGHjf eJJGdjjf(B: (3MjK HMKfG ai GdHGH GdChd WQb GdJHGOd GdJbdjOjI ef EjOGY , EQSGd h EYdGf h GdGSJMOGK GdWGQF YdjgG ai GdbGfhf GdaQfSi(B. (3h YGdL GdHGH GdKGfi h GdCNjQ eSCdI eOi GecGf EONGd Jdc GdWQb GdeSJMOKI Edi GdfXGe GdbVGFi GdeUQis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B342-357s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3JHGOd GhQGb GdeQGaYGJs; (3GdGWQGa aj GdNUheI GdbVGFjIs; (3ChQGb GdeQGaYGJs; (3GTNGU GdNUheI GdbVGFjIs; (3BdjGJ YedjI JHGOd GhQGb GdeQGaYGJs; (3GdfXGe GdbGfhfj dJHGOd GhQGb GdeQGaYGJs; (3hSGFd JHGOd GhQGb GdeQGaYGJs; (3GdGLQGAGJ GdGdcJQhfjI GeGe GdeMGces; (3GdWQb GdJbdjOjI dJHGOd GhQGb GdeQGaYGJs; (3OhQ QLGd GdbVGA aj JHGOd GhQGb GdeQGaYGJs; (3Gdeaghe GdbGfhfj dChQGb GdeQGaYGJ GdbVGFjIs; (3GdGNWGQ hGdGYdGf chSGFd QFjSjI dJHGOd GhQGb GdeQGaYGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes